Pengaruh Karakteristik Dewan Komisaris, Ukuran Perusahaan, Profitabilitas, dan Arus Kas Bebas terhadap Kebijakan Dividen - Wibowo, Ari; Setiany, Erna (Universitas Proklamasi 45, 2025)
The purpose of this study is to investigate how a company's dividend policy is influenced by the characteristics of its board of directors, business size, profitability, and free cash flow. The data to be analyzed in this study is quantitative secondary data obtained from the publication of financial statements by the Indonesia Stock Exchange (IDX). This study employed a purposive sampling strategy to select 180 manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2020 as the research sample. Normality tests, heteroskedasticity tests, autocorrelation tests, multicollinearity tests, coefficient determination tests, linear regression analyses, and t-tests are the analysis methods used. The t-test revealed that the characteristics of the commissioners had an influence on the company's dividend policy. While gender representation on the board of commissioners has a negative impact on dividend policy, the number of commissioners and free cash flow have a positive impact on dividend policy. Business dividend policy is not affected by the proportion of independent commissioners, company size, or profitability. However, dividend policy is significantly affected by free cash flow. The results showed that the proportion of independent commissioners in a company is usually lower than the number of commissioners owned by the company. Companies tend to allocate retained earnings to develop more profitable projects, thereby maximizing their profits. Companies that generate large inflows of free cash are more likely to make substantial dividend payments, thereby reducing waste on unprofitable projects.